Genomic Feature of a Rare Case of Mix Small-Cell and Large-Cell Neuroendocrine Lung Carcinoma: A Case Report - Zhu, Youcai; Zhang, Feng; Yu, Dong; Wang, Fang; Yin, Manxiang; Chen, Liangye; Xiao, Chun; Huang, Yueyan; Ding, Feng (Frontiers in Oncology, 2022)
Background Cases of both of small- (SCLC) and large-cell neuroendocrine lung carcinoma (LCNEC) were rarely reported. Although typical cases are morphologically distinct, the distinction between LCNEC and SCLC is still controversial, with some LCNECs showing close morphologies with SCLC. Here, we reported on a patient who had tumor with a mix of SCLC and LCNEC and uncovered these components’ histological and genomic features. Case Presentation A 59-year-old man was diagnosed with lung cancer and had resection surgery in our hospital. The H&E and immunohistochemistry staining revealed that the tumor had 30%–35% LCNEC and 65%–70% SCLC cells. The whole-exome sequencing (WES) identified no potentially actionable alteration in the tumor sample but found five alterations all with allele frequency over 90%, including TP53 p.R273H, MYH8 p.Q1814K, SLC17A6 p.W505L, PTPN5 p.M40I, and RB1 p.L267X. The genomic results supported that these two different components shared a similar dominant clonal origin. Furthermore, fluorescence in situ hybridization analysis revealed that the LCNECs have a higher copy number of MET than the SCLC component while without notable difference in the copy number of HER2 and TP53. Chemotherapy with pemetrexed and carboplatin was administrated for two cycles after the surgery. Although the chest CT showed remission in the lung, he was diagnosed with bone metastasis in 1 year later. Then, he received chemotherapy with etoposide and carboplatin but had severe side effect, leading to the discontinuation of the regime. Unfortunately, he returned to the local hospital with supportive care and died shortly after. Conclusion Based on these observations, we proposed that LCNEC and SCLC components in this patient may have a common clonal origin with dual mutations in TP53 and RB1, while the chromosome instability may cause multiple independent conversion that leads to LCNEC or SCLC morphologies.